Is arachidonic acid stimulation really a test for the response to aspirin? Time to think again?. (2nd January 2017) - Olechowski, Bartosz; Ashby, Alexander; Mariathas, Mark; Khanna, Vikram; Mahmoudi, Michael; Curzen, Nick
ABSTRACT: Introduction : Platelets play a key role in pathogenesis of atherothrombosis. Activated platelets initiate thrombus formation. Antiplatelet therapy (APT) modifies these properties. APT involves aspirin. The existence of 'aspirin resistance' is reported in many populations with cardiovascular disease. The prevalence of this phenomenon is highly variable, affecting more than 50% of patient subgroups in some papers. Areas covered : This review describes the prevalence of 'aspirin resistance', analyses why there is so much apparent variation and addresses whether the commonly used tests of aspirin response are in fact accurately assessing its functional performance. The clinical consequences if arachidonic acid(AA)-mediated assays do not accurately assess the functional performance of aspirin could be important. Expert commentary : Two important issues arise, firstly, that it can no longer be considered robust to use AA-induced platelet activation as a true diagnostic test of functional response to aspirin. It is clear that the output from PFT using AA as an agonist are not even a surrogate for the pharmacological activity of aspirin. Secondly, current data raise important and clinically relevant questions about, how AA stimulation induces clotting in individuals in whom aspirin is effective at its COX-1 target. The evidence indicates at least one recruitable, COX-1-independent pathway that is associated with vascular inflammation.